The Aesthetics of Endings in Ēvalds Vilks’s Short Stories During the Thaw: typological parallels with Italian Neorealism - Gūtmane, Zanda (Respectus Philologicus, 2026)
The article explores the aesthetics of endings in the short stories of Latvian writer Ēvalds Vilks (1923–1976) during the Thaw (1956–1964), searching for typological parallels with Italian neorealist cinema. While socialist realism ideology demanded optimistic and future-oriented endings, Vilks’s stories during the Thaw reveal an obvious transformation: from schematic endings in the early 1950s to pessimistic and closed endings in the late 1950s and later to ambivalent endings that combine the everyday with conditional hope. Based on the concepts of open and closed structures in narratology, the study analyzes twenty-five stories to identify structural and thematic trends. The comparative approach shows that Vilks’s prose, which focuses on ordinary people and everyday life, resonates with the narrative strategies of neorealism, which emphasized the unresolved, tragic, or ambivalent nature of endings. Thus, Vilks’s endings demonstrate a move away from socialist realism towards a more authentic representation of human experience.